Rheumatoid lung nodules - Bouchentouf, Rachid (2020)
Rheumatoid arthritis (RA) is a systemic disease which can be associated with respiratory  involvement. The interstitial lung disease and pleural effusion are the most frequent thoracic manifestations of rheumatoid arthritis. The rheumatoid lung nodules are rare, appear  late in the course of the disease. Its clinical and radiographic presentation can be confused with tuberculosis, fungi infections and lung cancer. We present a case of rheumatoid lung  nodules in a 55 year-old woman with seropositive rheumatoid arthritis.